KETERLIBATAN PIHAK KETIGA YANG TIDAK TERIKAT KLAUSULA ARBITRASE DALAM SENGKETA ARBITRASE - Desy Rumuy Astuti; Sylvia Janisriwati; Hadi Mulyo Utomo (CALYPTRA, 2018)
The purpose of this thesis journal is to meet the graduation requirementfor the Bachelor of Law from the Law Faculty of Universitas Surabaya. Thepractical aim of this paper is to determine whether a third-party whom is not tiedto an arbitration clause could be treated as parties to an arbitration agreement, andthus be bound by the arbitration decision. In general, the settlement of arbitrationis based on the arbitration agreement written by the parties in a dispute. In thecase of quarrel between PT RII against PT PT ISI and PT BKDI, there is a third-party involved — PT BKDI — which was not bound by the arbitration clauses. Theinvolvement of the third-party was approved by Badan Arbitrase PerdaganganBerjangka Komoditi (BAKTI), but struck down by the Supreme Court due to thenon-binding nature of a written agreement of arbitration to said third party.Therefore, the decision of BAKTI was overturned. However, according to Article30 of Arbitration and Alternative Dispute Resolution Law, there is a possibility ofinvolvement from third-party in the arbitration case with some limitations. If theterms and conditions are met, the involvement of the third-party can be consideredlegally valid in the arbitration process.